2018
DOI: 10.1080/15384047.2016.1250981
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-326 sensitizes human glioblastoma cells to curcumin via the SHH/GLI1 signaling pathway

Abstract: Glioblastoma multiforme is the most malignant and common brain tumor in adults and is characterized by poor survival and high resistance to chemotherapy and radiotherapy. Among the new chemotherapy drugs, curcumin, a popular dietary supplement, has proven to have a potent anticancer effect on a variety of cancer cell types; however, it remains difficult to achieve a satisfactory therapeutic effect with curcumin using the traditional single-drug treatment. In this study, we found that expression of miR-326, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 38 publications
2
31
0
2
Order By: Relevance
“…It has been reported that multiple lncRNAs in the SNHG family, such as SNHG1 and SNHG5, can sponge miRNAs to regulate their expression in different cancers, including prostate cancer and gastric cancer, thus participating in the tumor growth (Li et al 2017;Zhao et al 2017). In addition, miR-326 has been demonstrated to inhibit the growth of various types of tumors including HCC (Kim et al 2014;Li et al 2015b;Cao et al 2016;Wu et al 2017;Zhang et al 2017;Yin et al 2018). However, the relationship between SNHG3 and miR-326 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that multiple lncRNAs in the SNHG family, such as SNHG1 and SNHG5, can sponge miRNAs to regulate their expression in different cancers, including prostate cancer and gastric cancer, thus participating in the tumor growth (Li et al 2017;Zhao et al 2017). In addition, miR-326 has been demonstrated to inhibit the growth of various types of tumors including HCC (Kim et al 2014;Li et al 2015b;Cao et al 2016;Wu et al 2017;Zhang et al 2017;Yin et al 2018). However, the relationship between SNHG3 and miR-326 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs, the same as lncRNAs, have long been widely recognized in malignancies. MiR-326 acted as a tumor suppressor in several malignancies and targeted different genes in glioma, endometrial cancer, and cervical cancer (Li et al 2015b;Wu et al 2017;Zhang et al 2017;Yin et al 2018). However, no studies have reported the interaction between SNHG3 and miR-326 in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal miR-326 expression is involved in the malignant phenotype of cancer. In glioma, ectopic miR-326 expression suppresses cell proliferation, colony formation, invasion and metabolic activity, reduces ATP and glutathione levels, induces apoptosis, causes cell cycle arrest at the G1 phase and improves the chemosensitivity of cells to curcumin (33,34,39,40). In gastric cancer, miR-326 over expression represses cell growth, migration and invasion (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Интересно, что miR-326 является интрагенной микро-РНК, располагающейся в первом интроне гена аррестина b1 (ARRB1). Комбинированное введение miR-326 и полифенола куркумина значительно снижало активность Shh/Gli1 пути в клетках глиомы [22]. При ингибировании двух других микро-РНК -miR-125b и miR-324 наблюдались высокие уровни Hh-зависимой генной экспрессии, приводящей к пролиферации глиальных клеток [23].…”
Section: Smo Gli1 Ptchunclassified
“…Введение miR-326 может являться новой стратегией терапии [35]. miR-326 ингибируется PI3-киназным каскадом [21] [ [20][21][22], [35], [37] miR-675-5p, ген которой находится внутри гена длинной некодирующей РНК Н19, играет роль в развитии ответа на гипоксию и гипоксия-опосредованном ангиогенезе [81] [81], [82] короткая длина зрелых микро-РНК ограничивает дизайн проб [101]. Несомненным преимуществом RNA-seq является возможность глубокого анализа дифференциальной экспрессии, в том числе поиска вариаций (SNP и др.…”
Section: (рис 2)unclassified